Investigation of Hungarian mushrooms for antibacterial activity and synergistic effects with standard antibiotics against resistant bacterial strains. (June 2016) - Liktor‐Busa, E.; Kovács, B.; Urbán, E.; Hohmann, J.; Ványolós, A.
Abstract: This study aimed to screen the antibacterial activity of 160 extracts of 40 mushroom species, collected in Hungary, against 11 standard bacterial strains and 9 clinical isolates. The further objective of this work was to evaluate the capacity of active fungal extracts to potentiate the action of antibiotics against resistant pathogens. Disc‐diffusion method was applied for screening of antibacterial activity of extracts. Microdilution method was used to determine minimum inhibitory concentrations. The active extracts were applied to different resistant micro‐organisms (multiresistant Acinetobacter baumannii and  Pseudomonas aeruginosa, vancomycin‐resistant Enterococcus faecium and MRSA), combined with commercial drugs. The synergism between extracts and antibiotics was assessed by double‐disc synergy assay and determination of fractional inhibitory concentration (FIC) with checkerboard technique. From 40 mushrooms included in this experiment, 16 species exhibited antibacterial effects with moderate to high potential. In general the chloroform extracts proved to be most active, while the aqueous and aqueous‐methanolic extracts demonstrated low or no activity. Fistulina hepatica, Tapinella atrotomentosa (syn. Paxillus atrotomentosus ) and Rhodocybe popinalis were the most active species; moreover, they can potentiate the action of cefuroxime against MRSA. Significance and Impact of the Study: In this study, 160 organic ( n ‐hexane, chloroform and 50% methanol) and aqueous extracts of 40 mushroom species were submitted to antibacterial screening assay. The antibacterial capacity of 18 species has been examined for the first time. Nineteen extracts of 16 species showed antibacterial effects with moderate to high potential. The extracts of Fistulina hepatica, Tapinella atrotomentosa and Rhodocybe popinalis exhibited not only broad antibacterial spectrum, but also synergistic activity with cefuroxime against MRSA. Our screening study proved that mushroom species are promising sources of potential antimicrobial molecules. The results serve as good starting point for selection of fungal species for detailed pharmacological and chemical investigation. Abstract : Significance and Impact of the Study: In this study, 160 organic ( n ‐hexane, chloroform and 50% methanol) and aqueous extracts of 40 mushroom species were submitted to antibacterial screening assay. The antibacterial capacity of 18 species has been examined for the first time. Nineteen extracts of 16 species showed antibacterial effects with moderate to high potential. The extracts of Fistulina hepatica, Tapinella atrotomentosa and Rhodocybe popinalis exhibited not only broad antibacterial spectrum, but also synergistic activity with cefuroxime against MRSA. Our screening study proved that mushroom species are promising sources of potential antimicrobial molecules. The results serve as good starting point for selection of fungal species for detailed pharmacological and chemical investigation.